Effect of Cardiac Rehabilitation on Glomerular Filtration Rate Using Serum Cystatin C Concentration in Patients With Cardiovascular Disease and Renal Dysfunction. Issue 2 (March 2022) - Hama, Tomoaki; Ushijima, Akiko; Goto, Tadahiro; Nagamatsu, Hirofumi; Morita, Norishige; Yoshimachi, Fuminobu; Ikari, Yuji; Kobayashi, Yoshinori
Abstract : Purpose: Among patients with chronic kidney disease (CKD), little is known about whether the effect of cardiac rehabilitation (CR) on renal function differs across baseline estimated glomerular filtration rate using the serum concentration of cystatin C (eGFRcys). The aim of this study was to evaluate the effect of CR on renal function in patients with CKD. Methods: We performed a retrospective cohort study of patients with CKD (15 ⩽ eGFRcys < 60 mL/min/1.73 m 2 ) who participated in our CR program for cardiovascular disease. First, the patients were divided into three groups according to the baseline severity of the eGFRcys: G3a, G3b, and G4 groups. We compared the eGFRcys before and after the CR in each group. Second, to determine the association of baseline eGFRcys with the effect of CR, we fitted a linear regression model using the percent change in the eGFRcys (%ΔeGFRcys) as an outcome. Results: Of the 203 patients, 122 were in G3a, 60 were in G3b, and 21 were in G4 groups. The mean improvement of eGFRcys in each group was 1.3, 3.1, and 4.8 mL/min/1.73 m 2, respectively. The %ΔeGFRcys was larger among patients with lower baseline eGFRcys (0.47% greater improvement of %ΔeGFRcys/one lower baseline eGFRcys; 95% CI, 0.23-0.72%). This association remained significant after adjustment for potential confounders (0.63% greater improvement of %ΔeGFRcys/one lower baseline eGFRcys; 95% CI, 0.35-0.91%). Conclusions: The effect of CR on renal function was greater in patients with worse renal dysfunction measured by eGFRcys. A CR program could be useful for patients with severe renal dysfunction and it might have a beneficial effect on their renal function. Abstract : The effect of cardiac rehabilitation on renal function was greater in patients with worse renal dysfunction measured by estimated glomerular filtration rate based on serum concentration of cystatin C. Cardiac rehabilitation could be performed in patients with severe renal dysfunction and might have a beneficial effect on their renal function.